1996
DOI: 10.1002/(sici)1097-4644(199610)63:1<37::aid-jcb3>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene alterations in primary, recurrent, and metastatic human bone tumors

Abstract: We investigated the structure and the expression of various oncogenes in three of the most common human bone tumors-osteosarcoma (36 samples from 34 patients), giant cell tumor (10 patients), and chondrosarcoma (18 patients)-in an attempt to identify the genetic alterations associated with these malignancies. Alterations of RB and p53 were detected only in osteosarcomas. Alterations of c-myc, N-myc, and c-fos were detected in osteosarcomas and giant cell tumors. Ras alterations (H-ras, Ki-ras, N-ras) were rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…38,39 Although we observed a high-level gain of 8q23-q24 in 24% of cases, MYC (8q24.12-q24.13) amplification has been reported to occur in only 7-12% of osteosarcomas. 40,41 Tarkannen et al 21 reported that a copy-number increase at 8q represents a statistically significant poor prognostic factor; we arrived at this same conclusion for 8q gains, but only when present in combination with losses of 13q14.…”
Section: Event-free Survival (Efs) In 41 Patients With Primary Tumorsupporting
confidence: 79%
“…38,39 Although we observed a high-level gain of 8q23-q24 in 24% of cases, MYC (8q24.12-q24.13) amplification has been reported to occur in only 7-12% of osteosarcomas. 40,41 Tarkannen et al 21 reported that a copy-number increase at 8q represents a statistically significant poor prognostic factor; we arrived at this same conclusion for 8q gains, but only when present in combination with losses of 13q14.…”
Section: Event-free Survival (Efs) In 41 Patients With Primary Tumorsupporting
confidence: 79%
“…Several proto-oncogenes are known to be expressed in osteosarcomas [3,17,19,26,30], but their roles in the pathogenesis of these tumors are incompletely understood. Likewise, the roles of proto-oncogenes in the development of other musculoskeletal lesions remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, H-ras mutations in chondrosarcoma have not been previously reported. On the contrary, it has been reported that none of six chondrosarcomas demonstrated ras gene mutations (K-ras, H-ras, and N-ras) at codons 12, 13, and 61 (15), and that neither of two chondrosarcomas showed H-ras mutation at codon 12 (16). This document would therefore seem to be the first report to verify the presence of H-ras mutation in a series of chondrosarcoma.…”
Section: Discussionmentioning
confidence: 53%
“…As for sarcomas, H-ras mutations have been reported in MFH, leiomyosarcoma, and rhabdomyosarcoma (11)(12)(13)(14); however, H-ras mutations have not been reported in chondrosarcomas. Moreover, H-ras mutations were not detected in two previous series of chondrosarcoma (15,16), and the contribution of H-ras mutation to dedifferentiation has not been fully examined.…”
mentioning
confidence: 96%